Despite Interventions, Emergency Flow Stagnates in Urban Western Canada - Kreindler, Sara A. (Healthc Policy, 2021)
PURPOSE: This paper reports the quantitative component of a mixed-methods study of patient flow in the 10 urban health regions/zones of Western Canada. We assessed whether jurisdictions differed meaningfully in their emergency flow performance, defined as mean emergency department length of stay (ED LOS). METHODS: We used hierarchical linear modelling to compare ED LOS across jurisdictions, based on nationally reported data for 2017 to 2018. We also explored 36-month performance trends. Admitted and discharged patients were analyzed separately. RESULTS: With the exception of one high performer, no region's performance differed significantly from average for both admitted and discharged patients. The regions' levels of performance remained largely static throughout the study period. CONCLUSIONS: Results precluded any mixed-methods comparison of high- and low-performing regions. However, they converged with our qualitative findings, which suggested that most regions were pursuing similar flow-improvement strategies with limited effectiveness. Deeper changes may be required to address persistent misalignment between capacity and demand.